2022
DOI: 10.36341/jomis.v6i1.1946
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Endorphine Massage Terhadap Kecemasan Pasien Pre Sectio Caesarea Di Rsud Engku Haji Daud

Abstract: Riskesdas 2018 data from Riau Archipelago Province shows that the most Sectio Caesarea deliveries occur to mothers with an age range of 45-49 years (27.66%), education D1/D2/D3/PT (36.95%), most occupations are private employees (42.30%), and live in urban areas (24.6%). When preparing for a cesarean section, the patient will be faced with the operation process, the safety of the baby, and himself. Untreated preoperative anxiety can lead to complications that result in surgery delays. Therefore, anxiety in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
0
0
1
Order By: Relevance
“…Pandemi covid-19 menunjukkan hal bahwa kesehatan mental adalah masalah public utama. Krisis yang dihadapi jika dikelola dengan tepat, mungkin menjadi peluang untuk transformasi persepsi social global dan intervensi diperlukan untuk menangani kesehatan mental [12] Penelitian dengan judul pengaruh endorphine masaage terhadap kecemasan pasien pre section caesaria di RSUD Engku Haji Daud menunjukkan ada pengaruh endorphine massage terhadap tingkat kecemasan pada ibu pre sectio caesaria [13]. Penelitian dengan judul pengaruh terapi pijat puggung terhadap skor stress pada iu postpartum di RSIA Sakina Idaman Hasil penelitian menunjukkan nilai rata-rata skor stres sebelum di berikan terapi pijat punggung adalah 19,05 dan nilai rata-rata skor stres sesudah diberikan terapi pijat pungung adalah 17,10.…”
Section: Metodeunclassified
“…Pandemi covid-19 menunjukkan hal bahwa kesehatan mental adalah masalah public utama. Krisis yang dihadapi jika dikelola dengan tepat, mungkin menjadi peluang untuk transformasi persepsi social global dan intervensi diperlukan untuk menangani kesehatan mental [12] Penelitian dengan judul pengaruh endorphine masaage terhadap kecemasan pasien pre section caesaria di RSUD Engku Haji Daud menunjukkan ada pengaruh endorphine massage terhadap tingkat kecemasan pada ibu pre sectio caesaria [13]. Penelitian dengan judul pengaruh terapi pijat puggung terhadap skor stress pada iu postpartum di RSIA Sakina Idaman Hasil penelitian menunjukkan nilai rata-rata skor stres sebelum di berikan terapi pijat punggung adalah 19,05 dan nilai rata-rata skor stres sesudah diberikan terapi pijat pungung adalah 17,10.…”
Section: Metodeunclassified
“…Non-pharmacological therapies can be used to relieve anxiety, such as relaxation, acupuncture, warm water compresses, and massage. Pharmacological treatment can be performed by administering drugs, although administration of drugs to pregnant women needs to be restricted (Anjani, 2022). Previous studies showed that pregnant women often chose non-pharmacological treatment than pharmacological treatment because the latter puts the unborn child at risk (Callanan, Tuohy, Bright, 2022).…”
Section: Introductionmentioning
confidence: 99%